High prevalence of jumper's knee and sonographic changes in Swedish elite junior volleyball players compared to matched controls - Gisslen, K.; Gyulai, C.; Soderman, K.; Alfredson, H. (British Journal of Sports Medicine, 2005)
Background: Jumper's knee is a common and troublesome condition among senior volleyball players, but its prevalence among elite junior players compared to matched non-sports active controls is not known.